Whitehall, the City and the politicisation of finance during the Cold War. The case study of Yugoslavia : 1979 – 1983 - Parrillo, Emanuele (2025)
The thesis, Whitehall, the City, and the Politicisation of Finance during the Cold War: The Case Study of Yugoslavia, 1979–1983, analyses the intersection of British foreign policy and global finance during a critical period of the Cold War. It explores how the Thatcher government sought to balance ideological commitments to free-market principles with the geopolitical objective of stabilising Yugoslavia after Tito’s death to prevent Soviet influence. The research is divided into four chapters, each addressing a different aspect of Britain’s financial and diplomatic response. Chapter One sets the context by outlining Yugoslavia’s strategic importance and the emergence of the petro- dollar debt cycle, examining British concerns over maintaining the status quo in the Balkan country after Tito’s death. Chapter Two investigates the attitudes within Whitehall and the Bank of England towards using financial incentives to support diplomatic objectives, revealing the Bank’s reluctance to interfere with the City’s commercial decisions. Chapter Three focuses on the role of the Export Credits Guarantee Department in both the making of British commercial policy and British foreign policy, analysing how economic interests and monetarist policies limited the Thatcher government’s ability to provide official support for Yugoslavia during its financial troubles. Chapter Four explores Britain’s participation in the international rescue operation, showing how political pressure from Western allies eventually compelled limited financial intervention in the context of a global debt crisis. Overall, the thesis argues that, notwithstanding the centrality of London as the foremost centre of the Euromarket, Britain’s ability to use sovereign loans and export credits as effective tools of statecraft was constrained by the Thatcher government’s adherence to monetarist policies and the Bank of England’s laissez-faire approach. The case study provides a nuanced view of the interplay between economics and geopolitics in the making of British foreign policy, illustrating how financial institutions, private banks, and economic ideologies shaped Britain’s Cold War diplomacy.